An integrated phytochemical, in silico and in vivo approach to identify the protective effect of Caroxylon salicornicum against cisplatin hepatotoxicity - Shaymaa A. Ramadan; Emadeldin M. Kamel; Reem S. Alruhaimi; Albandari Bin-Ammar; Madeha A. Ewais; Akef A. Khowailed; Emad H.M. Hassanein; Ayman M. Mahmoud (Elsevier, 2023)
Cisplatin (CIS) is a chemotherapeutic medication for the treatment of cancer. However, hepatotoxicity is among the adverse effects limiting its use. Caroxylon salicornicum is traditionally used for treating inflammatory diseases. In this investigation, three flavonoids, four coumarins, and three sterols were detected in the petroleum ether fraction of C. salicornicum (PEFCS). The isolated phytochemicals exhibited binding affinity toward Keap1, NF-κB, and SIRT1 in silico. The hepatoprotective role of PEFCS (100, 200 and 400 mg/kg) was investigated in vivo. Rats received PEFCS for 14 days and CIS on day 15. CIS increased ALT, AST and ALP and caused tissue injury along with increased ROS, MDA, and NO. Hepatic NF-κB p65, pro-inflammatory mediators, Bax and caspase-3 were increased in CIS-treated animals while antioxidants and Bcl-2 were decreased. PEFCS mitigated hepatocyte injury, and ameliorated transaminases, ALP, oxidative stress (OS) and inflammatory markers. PEFCS downregulated pro-apoptosis markers and boosted Bcl-2 and antioxidants. In addition, PEFCS upregulated Nrf2, HO-1, and SIRT1 in CIS-administered rats. In conclusion, PEFCS is rich in beneficial phytoconstituents and conferred protection against liver injury by attenuating OS and inflammation and upregulating Nrf2 and SIRT1.